The Theoretical Description for Ag2O2/Squaraine Dye – Metformin Electrochemical Determination - Tkach, Volodymyr V.; Kushnir, Marta V.; vanushko, Yana G.; Ostapchuk, Valentyna G.; Melnychuk, Svitlana P.; de Oliveira, Silvio Cesar; Parchenko, Volodymyr V.; Aksyonova, Ilona I.; Odyntsova, Vira M.; Yagodynets´Petro I.; Kormosh, Zholt O.; Luganska, Olga V.; et al. (Orbital: The Electronic Journal of Chemistry, 2020)
In this work, the electrochemical description for metformin electrochemical determination, assisted by Ag2O2 composite with squaraine dye, is evaluated from the theoretical point of view. Metformin oxidation is realized via assisted electrochemical 1,2,4-triazole formation, followed by its polymerization and N-oxidation. The correspondent mathematical model has been developed and analyzed by means of linear stability theory and bifurcation analysis. It has shown that the neutral and basic media are more efficient for metformin electrochemical determination than acidic media, due to the absence of the influences of non-protonated aminogroupsand, furtherly, pyridinic nitrogen atoms to double electric layer (DEL) ionic force, conductivity and impedance. In these conditions, the electrochemical instabilities are less capable to realize and, therefore, the linear dependence between the analyte concentration and the current of the system will be easier to obtain and maintain, as no side reaction or additional process, capable to compromise the monomer and (or) modifier stability is realized. DOI: http://dx.doi.org/10.17807/orbital.v12i4.1537